A modified relay autotuner for systems having large broadband disturbances. (August 2018) - Goodwin, Graham C.; Seron, Maria M.; Townsend, Christopher
Abstract: Relay autotuners are widely adopted in practice due to their inherent robustness and ease of use. The core idea has been in existence for three decades. Various practical embellishments have been proposed in the literature to deal with such issues as static loads, chattering and low frequency drift. The current paper is motivated by the use of relay autotuning to build and identify models for the control of blood glucose levels in type 1 diabetics. The blood glucose level is affected by large time varying disturbances with broad spectral content arising from carbohydrate consumption and exercise. Consequently, existing strategies for relay autotuning were found to be inappropriate for this problem. To deal with this class of problem we propose a modified relay autotuner incorporating a highly resonant filter. The paper gives theoretical support to the idea, briefly discusses associated implementation issues, suggests several extensions and embellishments and demonstrates its features via simulation studies. The method is also applied to the modelling of the insulin to blood glucose response in a type 1 diabetic.